ANALYSIS OF THE IMPACT OF SMARTPHONE USE ON STUDENTS’ LEARNING ACTIVITIES DURING THE COVID-19 PANDEMIC - Ema Nofita Sari1 Ema; Ida Wahyuni Ida (Journal of Pedagogical Content Knowledge, 2026)
The COVID-19 pandemic has transformed the learning process from face-to-face instruction to distance learning, making smartphones one of the primary learning media used by students. This study aims to analyze the use of smartphones in supporting students' learning activities during the COVID-19 pandemic and to identify their positive impacts, limitations, and implementation challenges. The research employed a qualitative phenomenological approach to explore students' learning experiences in using smartphones during distance learning. Data were analyzed descriptively by examining participants' experiences, behaviors, and perceptions regarding smartphone use in educational activities. The findings indicate that smartphones play an important role in facilitating access to learning resources, communication between teachers and students, and the implementation of online learning. However, smartphone use also presents several challenges, including decreased learning concentration, excessive use for non-academic purposes, internet connectivity constraints, and unequal access to digital devices. Therefore, the effective use of smartphones requires appropriate technology-based learning strategies and active supervision from teachers and parents to optimize learning outcomes. The study concludes that smartphones can serve as effective learning media when supported by proper instructional design and responsible digital learning practices.